Analisis Kesalahan Perubahan Bunyi Bahasa Indonesia pada Tuturan Mahasiswa BIPA Tingkat Pemula di Universitas Muhammadiyah Malang - Inez Carmitha; Arif Budi Wurianto; Sudjalil; Abdul Qadir Hakimi (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the form of sound change symptoms and the factors that cause sound changes. This study uses a descriptive qualitative approach. The research data is based on learning speaking skills for 9 meetings from 12 meetings with a duration of 30 minutes. The source of research data is based on the results of Zoom video recordings of the speaking learning process for BIPA students at the beginner level, totaling 1 student from Egypt and 2 students from Uzbekistan. The data collection technique used is the technique of recording, listening, and taking notes. The data analysis used is error analysis. The results obtained were found data forms of assimilation changes, data forms of vocal modifications, data forms of anapticsis sound epenthesis, data forms anapticsis sound paragog, data forms zeroization of syncope sounds, data forms zeroization of apocope sounds, data forms monophthong changes, lenisi form data. The factors that cause changes in sound assimilation, vocal modification, anaptiksis, zeroization, monophthong, and lenisi, so that educators can provide special training to students from Egypt and Uzbekistan in learning speaking skills. The impact of these sound changes resulted in differences in meaning and improper pronunciation.